Calocera tibetica sp. nov. (Dacrymycetaceae, Dacrymycetales) from southwestern China - Fan, Long-Fei; Wu, Ying-Da; Wu, Fang; Dai, Yu-Cheng (Phytotaxa, 2021)
A new gelatinous species, Calocera tibetica, is described from southwest China based on morphological and molecular evidence. It is characterized by stipitate, tough, gelatinous, dichotomously branched, dendroid or staghorn-like basidioma with blunt tips, subclavate to clavate basidia measuring 45.0–53.0 × 4.8–6.0 µm, and hyaline, oblong-ellipsoid to navicular, 3–4-septate mature basidiospores measuring 9.0–14.0 × 5.0–6.3 μm. In the phylogeny, the new species is closely related to C. viscosa and C. cornea based on the nITS + nLSU dataset, but C. viscosa has basidioma with sharp tips, pale yellow, 1-septate mature basidiospores; C. cornea has cylindrical, subulate, slightly branched basidioma, and sub-hyaline cylindrical to slightly curved-cylindrical, 1-septate mature basidiospores measuring 7–10 × 3–4.5 μm. The new species is unique by its 3–4-septate mature basidiospores among species of Calocera.